Value chain development in Indian Agriculture: Challenges and way forward - Kumar, Shiv; Jhajhria, Abimanyu; Kumar, Daksh (Indian Farming, 2021)
An orderly agricultural marketing system is pivotal to the efficient allocation of scarce resources. The recent farms legislations are rolled out not only to create a value chain system for efficient agricultural marketing, improving trade related infrastructure and strengthening value/supply chains of the agricultural commodities but also to transform agriculture into more efficient, sustainable, competitive and resilient.